Medical Check-ups and Counseling for Early Disease Detection and Health Knowledge Improvement - Andi Sulfikar; M. Alfian Rajab; Rindani Claurita Toba; Rusli Taher (Journal of Evidence-Based Community Health, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and hyperuricemia are among the major public health challenges in Indonesia. Health promotion and disease prevention efforts through medical check-ups and education are important strategies to increase public awareness and enable early detection of NCD risk factors. This community service program was conducted in Adatongeng Village, Turikale District, Maros Regency, involving 12 residents. The intervention consisted of three stages: anamnesis, vital signs examination including blood pressure, and blood sugar and uric acid level tests. Counseling was then provided on healthy lifestyle practices, including a balanced diet, regular physical activity, and the importance of routine medical check-ups. The results showed active community participation in both the examinations and educational sessions, as well as increased awareness of the importance of early detection and prevention of NCDs. This activity suggests that integrating medical check-ups and education is an effective strategy in health promotion and disease prevention efforts to improve community quality of life.